Aqueous Eucalyptus globulus leaf extract-mediated biosynthesis of MgO nanorods - Jeevanandam, J.; Chan, Stephanie; Ku, Y. (2018)
Plant-based biosynthesis is gaining attention in nanoparticle synthesis as an alternate to chemical and physical synthesis routes due to their non-toxic and environment friendly nature. Leaf extract-based biosynthesis further facilitates rapid synthesis of non-toxic biocompatible nanoparticle that possesses various applications in biomedical and pharmaceutical industry. Metal oxides, especially MgO nanoparticles, show tremendous applications in medical industry. Moreover, plant-based biosynthesized MgO nanoparticles showed improved biophysical and biochemical properties. In the current study, MgO nanorods (MgONRs) are synthesized using Eucalyptus globulus aqueous leaf extract. The results are highly significant as rod-shaped nanoparticles possess superior cellular penetration ability than other morphologies and can be valuable in medical applications. A preliminary experiment was performed to identify the required reaction time for nanorod formation using dynamic light scattering technique. Later, one-factor-at-a-time approach was followed to identify the effect of each process parameters on average particle size of MgONRs. The optimized parameters were used for the synthesis of smaller-sized MgONRs. Fourier Transform infrared spectroscopy analysis was conducted to identify and analyze the functional groups in the leaf extract and MgONRs. The functional groups from phytochemicals and their transformation from enol to keto-form were found to be responsible for nanoparticle formation. The transmission electron microscope analysis showed that the optimized parameters yield 6–8 nm width of stacked MgONRs. Thus, the present work demonstrated a simple and rapid biosynthesis route for MgO nanorod synthesis which can be beneficial in biosensing and therapeutic application.